Density of experience: An exploration of heritage and transformation through Kaparen in Gothenburg - Andersson, Lina (My University, 2021)
Situated on Stigbergstorget in Gothenburg is the old cinema Kaparen, built in 1940. Kaparen is one of few remaining cinemas in a rather preserved condition from this time. Hence a relatively unique cinema with a strong functionalistic character. During its lifetime, the building has undergone several renovations to serve new functions but is today empty and without maintenance. The history of Kaparen shows that the original purpose of a building may eventually be revised and change its original program or structure to meet the constant changes of society. This thesis aims to explore how such a transformation can be performed whilst respecting and preserving the identity of the original building. This is investigated through a design proposal of Kaparen with a focus on refurbishment and addition, rather than preservation. To test how the interplay of past and present can result in an enhanced architectural experience, the historical and current context is essential. A study of texts regarding architectural transformation, Swedish functionalism, and the development of cinemas as a new building typology together with an inventory are performed to deepen the understanding of the chosen site and building. From these, a design proposal is developed by iterations of drawings, spatial investigations in digital models, and visualizations. The result shows a holistic approach, where the overall experience has been stressed since a desire to highlight all time layers in the building would risk it becoming historically identity-less. In conclusion, it is evident that there is no absolute answer on how to approach our architectural heritage, but rather approaching each individual situation separately with the totality in mind.